Epistemic practices: A unified account of epistemic and zetetic normativity. - Fleisher, Will (Nous (0029-4624), 2025)
This paper presents the epistemic practices account, a theory about the nature of epistemic normativity. The account aims to explain how the pursuit of epistemic values such as truth and knowledge can give rise to epistemic norms. On this account, epistemic norms are the internal rules of epistemic social practices. The account explains four crucial features of epistemic normativity while dissolving some apparent tensions between them. The account also provides a unified theory of epistemic and zetetic normativity.